Quality management practices as a driver of employee satisfaction: exploring the mediating role of organizational image. Issue 1 (22nd February 2021) - Babu, Faisal; Thomas, Sam
Abstract : Purpose: Total quality management (TQM) has been a universally applienod management strategy to improve organizational performance and thereby to achieve competitiveness. Compared with the scholarly and practical attention paid to identify the consequences of implementing TQM practices, little is known about how those practices enhance organizational image and employee satisfaction. This paper aims to address that research gap and is designed to empirically prove the relationship between TQM practices, organizational image and employee satisfaction. Design/methodology/approach: A questionnaire-based survey of 285 employees including administrators, managers and heads of departments of 21 National Accreditation Board for Hospital and Healthcare providers-accredited hospitals in India was conducted. The proposed research model was tested using partial least squares based structural equation modelling. Findings: The results revealed that TQM practices have positive direct and indirect effects on employee satisfaction, confirming the partial mediation role played by organizational image in the relationship between TQM practices and employee satisfaction. Research limitations/implications: From the findings, leaders can understand that by implementing TQM practices, organizations can enhance image of the organization and bring high level of employee satisfaction. Originality/value: The study tries to answer questions largely ignored in the TQM literature: the effect of TQM practices on organizational image and employee satisfaction, and the mediating role of organizational image on TQM practices and employee satisfaction.